Pengaruh Kemampuan Kerja terhadap Efektivitas Organisasi pada Dinas Kebudayaan Provinsi Kepulauan Riau - Pertiwi, Dewi Utami; Akhyari, Edy; Yudiatmaja, Wayu Eko (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2014)
Workability is skills or skills to do a job that is only gained from practice. Effectiveness is a businessoutreach program as a system with limited resources and means to meet the goals and targets withoutcrippling it means and resources, and without putting undue pressure on the implementation. Two aspectswill be explored in this study takes place in Riau Islands Province Cultural Office by measuringthe effect on the effectiveness of the organizations ability to work with a quantitative approach that isassociative. The conclusion from this study is that there is 36.6% with product moment correlation calculation,there is no significant influence between the workability and effectiveness of the organizationCultural Office Riau Islands Province. and test results of determination coefficient of 13.4% with theprovisions of SPSS version 17, which means that there is a significant and positive effect among variablesworkability to variable organizational effectiveness. Riau Islands Province Cultural Department,while the remaining 86.6% influenced by other variables not examined.